Normalizing salt content by mixing native human airway mucus samples normalizes sample rheology - Markovetz, Matthew R.; Hibbard, Jacob E.; Plott, Lucas M.; Bacudio, Lawrence G.; Kissner, William J.; Ghio, Andrew; Kumar, Priya A.; Arora, Harendra; Hill, David B. (Frontiers in Physiology, 2023)
Across the globe, millions of people are affected by muco-obstructive pulmonary diseases (MOPDs) like cystic fibrosis, asthma, and chronic obstructive pulmonary disease. In MOPDs, the airway mucus becomes hyperconcentrated, increasing viscoelasticity and impairing mucus clearance. Research focused on treatment of MOPDs requires relevant sources of airway mucus both as a control sample type and as a basis for manipulation to study the effects of additional hyperconcentration, inflammatory milieu, and biofilm growth on the biochemical and biophysical properties of mucus. Endotracheal tube (ETT) mucus has been identified as a prospective source of native airway mucus given its several advantages over sputum and airway cell culture mucus such as ease of access and in vivo production that includes surface airway and submucosal gland secretions. Still, many ETT samples suffer from altered tonicity and composition from either dehydration, salivary dilution, or other contamination. Herein, the biochemical compositions of ETT mucus from healthy human subjects were determined. Samples were characterized in terms of tonicity, pooled, and restored to normal tonicity. Salt-normalized ETT mucus exhibited similar concentration-dependent rheologic properties as originally isotonic mucus. This rheology agreed across spatial scales and with previous reports of the biophysics of ETT mucus. This work affirms previous reports of the importance of salt concentration on mucus rheology and presents methodology to increase yield native airway mucus samples for laboratory use and manipulation.